Multifunctional carbon aerogels from typha orientalis for applications in adsorption: Hydrogen storage, CO2 capture and VOCs removal. (15th January 2023) - Cheng, Jiahao; Cheng, Xingxing; Wang, Zhiqiang; Hussain, Muhammad Bilal; Wang, Meixia
Abstract: Biomass-derived cellulose carbon aerogels with a 3D network structure were synthesized from Typha Orientalis (TO). The TO cellulose carbon aerogels feature light mass (3.65 mg/cm 3 ), super-hydrophobicity, and large specific surface areas (1840 cm 2 /g). Because of the outstanding microporous volume and the abundant functional groups, the TO carbon aerogels can be used as multifunctional adsorbent materials in different applications. The results demonstrate that the material has 0.6 wt% hydrogen storage capacity at room temperature, 16 mmol/g CO2, 123.31 mg/g o-xylene and 124.57 mg/g o-dichlorobenzene adsorption capacity. The o-xylene adsorption capabilities of the sample were reduced by just 12% after four thermal regeneration cycles, demonstrating the realistically good reusability of TO cellulose carbon aerogels and is expected to be applied to dioxin removal. The current research can offer a green approach to fabricating ultra-light TO cellulose carbon aerogels with promising applications in energy storage and environmental protection. In addition, the preparation can be applied for the fabrication of other multifunctional aerogels by solid waste for different applications. Graphical abstract: The present manuscript used Typha orientalis (TO) as inexpensive raw materials, with economical freeze-drying process for multifunctional adsorption carbon aerogels preparation, which have good efficiency in hydrogen storage, carbon capture and VOCs removal, promising to be used in continuous industrial application. Image 1 Highlights: 3D multifunctional cellulose carbon aerogels are prepared from Typha Orientalis. KOH activation provides porous structure with high surface area of 1840 cm 2 /g. Developed a conjecture process that can be used reliably in a variety of contexts. High adsorption capacity for H2, CO2 and VOCs. Adsorption laws for various dynamic diameters are thoroughly explained.